2013
DOI: 10.1200/jco.2012.44.5932
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Tumor Cells Harboring a Unique ALK Rearrangement in ALK-Positive Non–Small-Cell Lung Cancer

Abstract: ALK rearrangement can be detected in CTCs of patients with ALK-positive NSCLC by using a filtration technique and FA-FISH, enabling both diagnostic testing and monitoring of crizotinib treatment. Our results suggest that CTCs harboring a unique ALK rearrangement and mesenchymal phenotype may arise from clonal selection of tumor cells that have acquired the potential to drive metastatic progression of ALK-positive NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
227
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(240 citation statements)
references
References 31 publications
(3 reference statements)
8
227
4
1
Order By: Relevance
“…The ISET Ò module contains 10e12 wells, each containing 0.6-cm diameter membranes, capable of processing a 1-ml volume. Multiple clinical studies have used ISET Ò for CTC isolation (Chinen et al, 2013;Farace et al, 2011;Hofman et al, 2011;Ilie et al, 2014;Krebs et al, 2012;Pailler et al, 2013). ScreenCell Ò uses circular track-etched filters with a hydrophilic surface and cylindrical 7.5 or 6.5-mm pores for filtering fixed or live samples, respectively (Desitter et al, 2011).…”
Section: Two-dimensional Microfiltration Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ISET Ò module contains 10e12 wells, each containing 0.6-cm diameter membranes, capable of processing a 1-ml volume. Multiple clinical studies have used ISET Ò for CTC isolation (Chinen et al, 2013;Farace et al, 2011;Hofman et al, 2011;Ilie et al, 2014;Krebs et al, 2012;Pailler et al, 2013). ScreenCell Ò uses circular track-etched filters with a hydrophilic surface and cylindrical 7.5 or 6.5-mm pores for filtering fixed or live samples, respectively (Desitter et al, 2011).…”
Section: Two-dimensional Microfiltration Systemsmentioning
confidence: 99%
“…Ò Size, Deforma-bility Filters fixed samples through 8-mm pores, 10e12 wells can process 1 mL each, clusters observed (Chinen et al, 2013;Farace et al, 2011;Hofman et al, 2011;Ilie et al, 2014;Krebs et al, 2012;Pailler et al, 2013;Vona et al, 2000) ScreenCell Ò Hydrophilic surface, fixed/live samples, 7.5/6.5-mm pores (Desitter et al, 2011;Freidin et al, 2014) 2D, Lithography CellSieveä Constructed from a transparent, flexible, non-fluorescent photoresist, 7-mm pores (Adams et al, 2014a(Adams et al, , 2014b(Adams et al, , 2015 Flexible Micro Spring Array (FMSA)…”
Section: D Track-etched Isetmentioning
confidence: 99%
“…In principle, the concordance of genomic alterations between tumor biopsies and CTCs/ctDNA has been demonstrated by several reports, both for EGFR mutations (62)(63)(64) and ALK translocations (50,54,65), leading to the inclusion of CTCs/ ctDNA in clinical trials as prognostic/predictive biomarkers. The results of these studies suggest that monitoring EGFR mutations or EML4-ALK rearrangements in the circulating compartment can reveal therapy resistance also prior to radiological progression evidence, thus guiding the therapeutic decision in the patient clinical course (62,65) (32,68).…”
Section: Exploring the Metastatic Potential Of Lung Ctcsmentioning
confidence: 99%
“…Several studies associate CTC number to OS and/or PFS of metastatic NSCLC patients (32,33,48,57), meanwhile others do not find these associations (70,71). Many small trials have also demonstrated the association between CTC count and therapy efficacy, comparing the count before and after therapy (38,(72)(73)(74), or during target therapy, in order to detect the onset of resistance mutations (50,54,62,66,75). Even though most data suggest the utility of CTCs as biomarkers for assessing prognosis and monitoring therapy response in NSCLC, these assays are still not used in routine clinical practice, mainly due to the lack of standardized procedures allowing reliable and reproducible results that could be compared among different cohorts of patients.…”
Section: The Long Road Towards Clinical Utilitymentioning
confidence: 99%
“…In a recent study by Pailler et al, ALKrearranged CTCs expressed a mesenchymal phenotype contrasting with heterogeneous epithelial and mesenchymal marker expressions in NSCLC tumors. 33 Moreover, preclinical data 34 also showed that K-ras overexpression will reduce the expression of E-cadherin, which means that the patients with K-ras mutation are also more likely to express a mesenchymal phenotype. As ALK fusion and K-ras mutation seem to be import factors for primary resistance to EGFR-TKIs, EMT phenotype might be the underlying factor for resistance to EGFR-TKIs.…”
Section: Cancer Therapymentioning
confidence: 99%